Advanced technologies and novel solutions for a competitive and sustainable European biogas sector.
The EU-funded ATBEST project recently hosted its final international conference from 7 to 8 September 2016 in Linkoping, Sweden, where it outlined its toolbox of innovative solutions to support and promote the future growth and sustainability of the European biogas sector.